Overview of the Impending Changes in the Family Justice Landscape - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2014)
Singapore’s family justice landscape is set to witness a sea-change when the key features of the new Family Justice Act, as well as recommendations from the Committee for Family Justice (chaired by the Senior Minister of State for Law and Education, Justice VK Rajah, and Justice Andrew Phang), materialise in the months ahead.